Declining Interest in Reading in Elementary School Students: An Analysis of Inhibiting Factors and Their Impact on Learning Achievement - Dhea Ayu Anggraini; Ratna Ekawati; Slamet Arifin; Dedi Kuswandi; M. Ramli (Green Publisher Indonesia, 2025)
Interest in reading is a crucial foundation for achieving students' academic success, particularly at the elementary school level. However, in recent years, there has been a noticeable decline in reading interest among elementary school students, which has significantly impacted their academic performance. This study aims to analyze the inhibiting factors that affect students' interest in reading and their impact on learning achievement. The method employed is a literature review, gathering data from various studies published within the last five years. The findings indicate that low reading interest is caused by a lack of motivation, limited access to appropriate reading materials, and non-innovative learning approaches. Furthermore, the school and family environments also play a vital role in shaping students' reading habits. This research underscores the need for collaboration between schools and families to create an environment that fosters a habit of reading. By understanding the factors that hinder reading interest, it is hoped that improvements in students' academic achievement can be achieved, better preparing them for future educational challenges.